Low‐Cost Intrinsic Flame‐Retardant Bio‐Based High Performance Polyurethane and its Application in Triboelectric Nanogenerators - Xiaoyu Zhang; Xixian Yan; Fanglei Zeng; Hao Zhang; Peiyao Li; Haiyang Zhang; Ning Li; Qingbao Guan; Zhengwei You (Advanced Science)
Abstract Flammability is a significant challenge in polymer‐based electronics. In this regard, triboelectric nanogenerators (TENGs) have enabled a safe means for harvesting mechanical energy for conversion into electrical energy. However, most existing polymers used for TENGs are sourced from petroleum‐based raw materials and are highly flammable, which can further accelerate the spread of fire and harm the ecological environment. In addition, the existing intrinsic flame‐retardant TENGs are not elastic at room temperature, which may potentially damage the flexible equipment and harm firefighters. This study presents an intrinsic flame‐retardant bio‐based elastic phytic acid polyurethane (PUPA) synthesized using a simple and efficient one‐pot polycondensation. The cross‐linked structure and polar phosphorus‐containing segments of PUPA are fabricated into PUPA‐TENG, demonstrating a superior elasticity (elongation up to 660%), flame retardancy (UL94 V‐0), impact resistance (34.71 MJ m−3), and dielectric constant (Dk = 9.57). Consequently, this study provides a simple strategy for tailoring TENGs toward environmentally friendly and secure power generators and electronics, which can effectively reduce fire hazards and potentially be applied to other fire‐risk fields such as personal protection, firefighting, and new energy.